BENALU DALAM KARYA SENI LUKIS SUREALIS - Khairunas M Abdi; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2021)
The purpose of the creation of this final work is to visualize consumptive behavior as a concept into painting. Showing the bad impact of human behavior that is like parasites on social life. The methods used in the process of creating this final work are: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, (5) Completion. The results of the visualization of human behavior such as parasites reveal that many things occur in the environment that cannot distinguish between what acts as parasite and which acts as the host, so there is a lot of bitterness, misery, for the little people due to the presence of these harmful people. . The titles of these ten final works are: Parasites, Nuts, Forced, Blackmail, Interrogation, Karma, Ignorance, Satan, Regret, Sorrow and Anger of a Girl.Keywords: Benalu, Painting Art, Surreal